Challenges in the management of chronic noncommunicable diseases by Indonesian community pharmacists - Puspitasari HP; Aslani P; Krass I. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Objectives: We explored factors influencing Indonesian primary care pharmacists' practice in chronic noncommunicable disease management and proposed a model illustrating relationships among factors. Methods: We conducted in-depth, semistructured interviews with pharmacists working in community health centers (Puskesmas, n=5) and community pharmacies (apotek, n=15) in East Java Province. We interviewed participating pharmacists using Bahasa Indonesia to explore facilitators and barriers to their practice in chronic disease management. We audiorecorded all interviews, transcribed ad verbatim, translated into English and analyzed the data using an approach informed by "grounded-theory". Results: We extracted five emergent themes/factors: pharmacists' attitudes, Puskesmas/apotek environment, pharmacy education, pharmacy professional associations, and the government. Respondents believed that primary care pharmacists have limited roles in chronic disease management. An unfavourable working environment and perceptions of pharmacists' inadequate knowledge and skills were reported by many as barriers to pharmacy practice. Limited professional standards, guidelines, leadership and government regulations coupled with low expectations of pharmacists among patients and doctors also contributed to their lack of involvement in chronic disease management. We present the interplay of these factors in our model. Conclusion: Pharmacists' attitudes, knowledge, skills and their working environment appeared to influence pharmacists' contribution in chronic disease management. To develop pharmacists' involvement in chronic disease management, support from pharmacy educators, pharmacy owners, professional associations, the government and other stakeholders is required. Our findings highlight a need for systematic coordination between pharmacists and stakeholders to improve primary care pharmacists' practice in Indonesia to achieve continuity of care.